Aid Eﬀectiveness: From Project Appraisal to Strategic Impact Evaluation - D. A. Degterev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
A sheer volume of multibillion concessional ﬂows from leading international donors makes monitoring and evaluation of aid projects a sine qua non of development discourse and practice. The assessment criteria vary signiﬁcantly and depend on the objectives and interests of donor countries promoted through development cooperation.This paper examines national systems of monitoring and evaluation of aid eﬀectiveness established by leading donors. Among the most noticeable recent trends the author emphasizes a transition from aid eﬀectiveness to development eﬀectiveness paradigm and an inclusion of indicators of diplomatic engagement and security provision in evaluation matrices.Special attention is paid on the hierarchy of goals in national systems of development cooperation, which is illustrated with an example of the United States. The US case shows key principles of ensuring policy coherence at diﬀerent levels of goal-setting — from the National Security Strategy to planning individual projects and programs. In conclusion the author shares his view on the applicability of foreign experience in evaluating development assistance projects in the Russian Federation.